Active Vibration Suppression of Rotor Unbalance through an Adaptive Control Method Based on Self-adjusting of PD Gain - Yao, Jian-Fei; Dai, Jia-Bao; Liu, Liang; Yang, Feng-yu; Gao, Shu-cheng (Journal of Vibration Testing and System Dynamics, 2026)
The attention is conﬁned to the vibration suppression of rotor unbalance in this paper. A method to control synchronous vibration due to rotor unbalance in rotor-bearings system is proposed which uses active magnetic actuator (AMA) to produce active control force to suppress rotor’s vibration. A model reference adaptive control strategy based on self-adjusting of Proportional and Diﬀerential gain is adopt for producing active electromagnetic force. First the model of rotor-bearing system with AMA and the ideal reference model are established using the ﬁnite element and the state space method. Then on the basis of PD feedback, the adaptive control of feedforward and unbalance compensation is considered. An active vibration control scheme for controlling transverse vibration of rotor due to unbalance excitation is designed. Finally, numerical example and simulated analysis for controlling synchronous vibration of rotor are carried out. The simulation results indicate that the proposed approach can eﬀectively suppress the synchronous vibration caused by rotor unbalance using the electromagnetic force.